Referendum as a response to the Peruvian representative crisis - Miró Quesada Rada, Francisco (2019)
The article addresses, first from a systematic perspective, the legal and constitutional configuration of the referendum in Peru. Next, its employment is analyzed as a political tool during the political crisis that our country is passing through.